Indonesia dalem api dan bara - Tjamboek Berdoeri, 1900-1974 (Jakarta : Elkasa, 2004)
Author's account during Dutch and Japanese occupation in Indonesia
Includes bibliographical references
Keywords: Tjamboek Berdoeri, -- 1900-1974; Peranakan (Asian people) -- Indonesia -- Java -- Biography; Indonesia -- History -- 1798-1942; Indonesia -- History -- Japanese occupation, 1942-1945